Encapsulated composite catalyst and application thereof in preparation of low-carbon olefin by oxidative cracking of naphtha

Through the application of encapsulated composite catalyst, combined with the combination of oxide oxygen carrier and molecular sieve and hydrothermal preparation technology, the problems of large investment in naphtha catalytic cracking technology are solved, and high reaction temperature are achieved. High efficiency and low energy consumption are achieved Naphtha oxidation and cracking improve the selectivity of low-carbon olefins and the coke resistance of catalysts.

CN119425777AActive Publication Date: 2025-02-14XIANGTAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411720215.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing catalytic cracking technology of naphtha has problems such as large equipment investment, high reaction temperature, harsh process conditions, low production capacity, many side reactions, large energy consumption, large safety hazards, and difficult product distribution to adjust. The molecular sieve catalyst is prone to deactivate, The regeneration process is complex and costly.

Method used

Using encapsulated composite catalyst, it is prepared by combining oxide oxygen carriers (such as CaMnO3, CaMn0.8Cu0.2O3, etc.) with molecular sieves (such as ZSM-5, Beta, etc.), and is prepared by hydrothermal seed induction method to form a core-shell structure. , inhibits the sintering and agglomeration of metal oxide nanoparticles, and provides thermal energy through the oxidation and reduction reaction of oxygen carriers, achieving efficient oxidation and cracking of naphtha.

Benefits of technology

Improve naphtha conversion rate and low-carbon olefin selectivity, reduce reaction temperature and energy consumption, reduce the generation of carbon deposits and cokes, avoid safety hazards in the process of air separation and oxygen production, and improve the coke resistance of the catalyst and recycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides an encapsulated composite catalyst, the composition of the encapsulated composite catalyst is as follows: an oxide oxygen carrier (at) molecular sieve, the oxide oxygen carrier is selected from any one of CaMnO3, CaMn0. 8Cu0. 2O3, MgMn2O3, NiMn2O3, Fe2O3, Mn2O3 and Co3O4, and the molecular sieve is selected from any one of a ZSM-5 molecular sieve, a Silicate-1 molecular sieve and a Beta molecular sieve. The catalyst overcomes the problems of easy aggregation of metal ions, blockage of a pore structure, weak interaction force between metal and the molecular sieve and the like in the traditional metal molecular sieve preparation process; and the defect that the metal oxide oxygen carrier is easy to sinter and agglomerate under a high-temperature reaction condition is effectively inhibited. The invention also provides application of the encapsulated composite catalyst in preparation of low-carbon olefin by oxidative cracking of naphtha, transformation of cracking reaction from high self-heat absorption to self-heat supply is realized, process consumption is greatly reduced, the conversion rate is high, and the mass selectivity of low-carbon olefin is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparing light olefins through oxidative cracking of naphtha, and in particular to an encapsulated composite catalyst and application thereof in preparing light olefins through oxidative cracking of naphtha. Background Art

[0002] Light olefins (C2 = ~ C4 = ), such as ethylene, propylene, 1,3-butadiene, etc., as the bulk products of modern chemical industry, are widely used in plastics, rubber, medicine, fine chemicals and other fields. At present, the most commonly used methods for producing ethylene and propylene are steam thermal cracking and catalytic cracking of hydrocarbon raw materials (mainly naphtha).

[0003] For example, CN101190865A discloses a method for producing ethylene and propylene by catalytic oxidation cracking of naphtha. 10 The hydrocarbon naphtha is used as the raw material. The raw hydrocarbon is vaporized and mixed with the oxygen-containing gas. The reaction temperature is 580-750°C, the reaction pressure is 0.05-0.5MPa on a gauge pressure, and the weight space velocity is 0.5-1.5 hours. -1 Under the conditions that the weight ratio of water to naphtha is 0 to 5:1 and the molar ratio of naphtha to O2 in the raw mixed gas is 0.3 to 5.0:1, the raw mixed gas contacts with the catalyst to react and generates ethylene and propylene, wherein the catalyst used is selected from at least one of ZSM-5 / mordenite intergrowth molecular sieve or ZSM-5 / β zeolite intergrowth molecular sieve.

[0004] Steam thermal cracking of naphtha has the disadvantages of large equipment investment, high reaction temperature, harsh process conditions, high requirements for reactor tube materials, large losses, and low production capacity. Catalytic cracking has oxygen co-feed, which makes the cracking reaction difficult to control and is prone to various side reactions such as over-cracking, oxidative dehydrogenation, and deep oxidation. During the catalytic cracking reaction, CO X Excessive emissions; high reaction energy consumption, the oxygen production process requires a high-energy air separation device (accounting for about 1 / 3 of the energy consumption of the entire dehydrogenation process); petroleum hydrocarbons and O2 are mixed as feed materials, which poses a huge safety hazard during the reaction and is difficult to apply industrially; the distribution of cracking reaction products is not easy to flexibly adjust, and other technical issues.

[0005] Zeolite molecular sieves are often used in the industrial production of traditional naphtha catalytic cracking, such as: ZSM-5 molecular sieve, Y-type molecular sieve, Beta molecular sieve, SAPO molecular sieve, etc. However, during the catalytic cracking process, the molecular sieve catalyst is easily deactivated due to carbon deposition, poisoning, etc., which reduces the catalytic efficiency. Although the molecular sieve catalyst can be regenerated by air / oxygen and compensate for part of the reaction heat, the reaction process is still highly endothermic. In addition, the regeneration process is complicated and costly, which further increases the production cost and difficulty. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide an encapsulated composite catalyst and its application in the oxidation cracking of naphtha to produce light olefins.

[0007] The technical solution of the present invention is: An encapsulated composite catalyst, the encapsulated composite catalyst comprises: oxide oxygen carrier@molecular sieve, wherein the oxide oxygen carrier is selected from CaMnO3, CaMn 0.8 Cu 0.2 Any one of O3, MgMn2O3, NiMn2O3, Fe2O3, Mn2O3, Co3O4, and the molecular sieve is any one of ZSM-5 molecular sieve, Silicate-1 molecular sieve and Beta molecular sieve.

[0008] Preferably, the method for preparing the encapsulated composite catalyst comprises: preparing CaMnO3, CaMn by a sol-gel method. 0.8 Cu 0.2 O3 perovskite metal oxide oxygen carrier or MgMn2O3, NiMn2O3 spinel oxide oxygen carrier, or Fe2O3, Mn2O3, Co3O4 single-component metal oxide oxygen carrier prepared by precipitation method, and then the encapsulated composite catalyst is prepared by hydrothermal seed induction method.

[0009] Preferably, the step of preparing the encapsulated composite catalyst by the hydrothermal seed induction method comprises: adding 1-3 g of seed molecular sieve to a mixed solution of a silicon source, a template and 20-30 mL of deionized water to form a mixed aqueous solution, and stirring at 20-30°C for 2-3 h; then adding 0.5-1.5 g of an oxide oxygen carrier and 0.03-0.05 mol of a surfactant to 20-30 mL of deionized water, and stirring at room temperature for 1-3 h to obtain an oxide oxygen carrier mixed suspension; mixing the mixed aqueous solution with the oxide oxygen carrier mixed suspension to form a mixed system, stirring the mixed system at 80-90°C for 2-5 h to obtain a precursor mixed suspension, and aging the precursor mixed suspension for 24-48 h, and then hydrothermally heating the precursor mixed suspension at 170-180°C for 1-3 h; centrifuging the precursor mixed suspension, washing with deionized water 2-4 times, and obtaining a solid product, and the solid product is heated at 100 After drying in an oven at ℃-120℃ for 8-12 h, the catalyst was calcined in a muffle furnace at 500-600℃ for 8-12 h, cooled to room temperature and ground into a powdered solid with a size of less than 10 meshes to prepare an encapsulated composite catalyst.

[0010] More preferably, the seed molecular sieve is selected from any one of ZSM-5 molecular sieve, Silicate-1 molecular sieve and Beta molecular sieve.

[0011] Further preferably, the molar ratio of the silicon source to the template is 0.5-1.0: 0.15-0.25.

[0012] More preferably, the silicon source is selected from any one of methyl orthosilicate, ethyl orthosilicate, silica sol, polyethoxydisiloxane, methyltrimethoxysilane and methyltriethoxysilane.

[0013] More preferably, the template agent is selected from any one of tetrapropylammonium hydroxide, hexadecyltrimethylammonium bromide, triethylamine and cyclohexylamine.

[0014] Further preferably, the surfactant is selected from polyvinyl pyrrolidone.

[0015] Further preferably, the mass ratio of the seed molecular sieve to the metal oxide oxygen carrier is 2-3:1.

[0016] Preferably, the sol-gel method comprises: preparing the perovskite and spinel oxygen carriers according to their molecular formulas of CaMnO3, CaMn 0.8 Cu 0.2 O3, MgMn2O3, NiMn2O3, confirm the metal cation composition, and weigh the nitrate containing the corresponding cation and dissolve it in deionized water to form a nitrate solution, and then add citric acid and ethylene glycol to the nitrate solution to form a mixed system, and finally heat the mixed system at 70 ℃ -90 ℃ with stirring to form a sol, and the sol is dried at 80 ℃ -100 ℃, calcined at 350 ℃ -500 ℃ for 1 h -3 h, and calcined at 850 ℃ -1000 ℃ for 6-9 h, cooled to room temperature and ground to obtain oxide oxygen carriers doped with different metals.

[0017] Preferably, citric acid is added in a molar ratio of 1.5-3:1 to the metal cation, and ethylene glycol is added in a molar ratio of 1-2.5:1 to the citric acid.

[0018] Preferably, the precipitation method comprises: weighing a nitrate of a single-component metal oxide oxygen carrier corresponding to a cation and dissolving it in deionized water, wherein the molar concentration of the metal cation is 0.1-0.2 mol / L, to obtain a metal precursor solution; then accurately weighing sodium carbonate and dissolving it in deionized water, wherein CO3 2-The molar concentration is 0.3-0.4 mol / L. Under stirring, the sodium carbonate solution is added dropwise to the metal precursor solution until the pH value of the mixed solution is 10-11. The mixed solution is continuously stirred at 90°C-100°C for 20-24 h, and then centrifuged and washed until neutral. The obtained solid product is dried at 70°C-90°C overnight, and then calcined in a muffle furnace at 550°C-700°C for 5 h-7 h to prepare a single-component metal oxide oxygen carrier.

[0019] The room temperature is generally 20°C-30°C, and overnight is generally 10-20 hours.

[0020] The present invention also provides a novel method for preparing light olefins by oxidative cracking of naphtha, wherein the naphtha raw material is contacted with a catalyst, and an oxidative cracking reaction of the catalyst is carried out under the conditions of 500-800°C, an air flow rate of 25-200 mL / min, a naphtha feed amount of 0.1-0.5 g, and a reaction time of 300-420 s per oxidation-reduction cycle, and the reaction flow is separated to obtain the target product light olefins. The catalyst is any one of the above encapsulated composite catalysts; Alternatively, the catalyst is selected from CaMnO3, CaMn 0.8 Cu 0.2 Any one of O3, MgMn2O3, NiMn2O3, Fe2O3, Mn2O3, Co3O4.

[0021] Preferably, after the cracking reaction, the encapsulated composite catalyst is oxidized and regenerated by an air flow of 80-200 mL / min.

[0022] The present invention is further explained and illustrated below. The naphtha chemical chaining oxidation cracking process of the present invention is based on chemical chaining combustion technology. By constructing an encapsulated composite catalyst with oxygen carrying and oxidation cracking capabilities, in the absence of gaseous oxygen, high-efficiency oxidation cracking of naphtha to produce low-carbon olefins is achieved. This process includes oxidation cracking and oxygen carrier regeneration steps. In the oxidation cracking reaction, naphtha is cracked on the active component to form low-carbon olefins, and at the same time, the lattice oxygen in the metal oxide oxygen carrier oxidizes part of the generated hydrogen into water vapor in situ, promoting the balance of the cracking reaction to move in the positive direction, and improving the conversion of the substrate; after the reaction is completed, the oxygen carrier that has lost the lattice oxygen can be oxidized and regenerated in the air, replenishing the lattice oxygen while removing carbon deposits, and restoring the catalyst reaction activity.

[0023] Compared with the traditional industrial naphtha cracking technology, the chemical chain oxidation cracking technology uses the effect of lattice oxygen as an oxygen carrier to decompose the cracking reaction into two gas-solid reactions (oxidation reaction and reduction reaction), which not only eliminates the resource- and energy-intensive air separation process, but also avoids direct contact between naphtha and air, eliminating potential safety hazards, allowing the reaction to be carried out under a higher partial pressure of petroleum hydrocarbons, and further improving the reaction conversion rate. At the same time, the oxidation and regeneration process of the lattice oxygen consumed by the oxygen carrier in the air will release a large amount of heat to supply the cracking reaction, realizing the self-heating operation of the cracking process, and greatly reducing the process energy consumption.

[0024] In traditional naphtha catalytic oxidation cracking technology, the intracrystalline diffusion limit of the micropores of zeolite molecular sieves inhibits the diffusion of reactant and product molecules, resulting in the acidic center of the zeolite molecular sieve being easily deactivated by carbon deposition. Although zeolite molecular sieves can form a hierarchical structure through desiliconization or dealumination post-treatment to improve the mass transfer process of the cracking reaction, the post-treatment process is difficult to control and the expanded pore structure is easily destroyed during the reaction, which seriously limits its further industrial application. In addition, the lattice oxygen of metal oxide oxygen carriers is thermodynamically stable under low temperature conditions, and high temperature conditions (>750 ℃) are usually required for naphtha oxidation cracking reactions. Under high temperature conditions, metal oxide oxygen carriers are prone to sintering and agglomeration, resulting in coking, which leads to a decrease in catalytic performance.

[0025] Based on this, the present invention designs and constructs a series of encapsulated composite catalysts (oxide oxygen carrier @ molecular sieve), encapsulates metal oxide oxygen carrier nanoparticles inside the molecular sieve, and applies to naphtha chemical chain oxidation cracking reaction to produce light olefins. Wherein, the metal oxide oxygen carrier categories include: perovskite type, spinel type, single component metal oxide, wherein the metal composition is transition metal and / or rare earth metal, and the metal oxide oxygen carrier is synthesized by sol-gel method or precipitation method. And using several molecular sieves as seeds and using hydrothermal seed induction method, the metal oxide oxygen carrier is encapsulated inside the molecular sieve without changing the molecular sieve topology. The core-shell structure of the encapsulated composite catalyst can effectively inhibit the sintering and agglomeration of metal oxide nanoparticles. In addition, the metal oxide oxygen carrier lattice oxygen is used to promote the forward movement of the cracking reaction through the selective hydrogen burning reaction, thereby improving the cracking reaction activity; at the same time, the generation of molecular sieve coking can be inhibited by oxidation reaction to improve its coke resistance. This effectively improves the cracking reaction performance and recyclability of the composite catalyst.

[0026] The calculation method of yield and selectivity in the embodiment of the present invention is as follows: FU Li97Plus and Techcomp 7900 gas chromatographs were used to analyze the gas product components (low-carbon olefins, alkanes, aromatics, CO X, carbon deposition) and content, and their content is determined by external standard method. Naphtha conversion rate and product selectivity are calculated based on mass, and the specific formula is as follows:

[0027]

[0028] The target products are light olefins, and our goal is to achieve high conversion rate and high selectivity for light olefins.

[0029] Compared with the prior art, the present invention has the following beneficial effects: 1. The encapsulated composite catalyst (oxide oxygen carrier @ molecular sieve) of the present invention overcomes the problems of easy aggregation of metal ions, clogging of pore structure and weak interaction between metal and molecular sieve in the preparation process of traditional metal molecular sieves; at the same time, it effectively inhibits the disadvantage that metal oxide oxygen carriers are easy to sinter and agglomerate under high temperature reaction conditions.

[0030] 2. The rich and appropriately strong acidic centers of the zeolite molecular sieve in the encapsulated composite catalyst of the present invention can effectively reduce the activation energy of CH breakage of hydrocarbons in the naphtha substrate, and effectively reduce the temperature of the naphtha cracking reaction; in the process of naphtha chemical chain oxidation cracking, the SHC reaction of the oxygen carrier lattice oxygen and the by-product hydrogen of the cracking reaction causes the reaction equilibrium to move forward, thereby promoting the conversion of the substrate.

[0031] 3. The oxidation reaction of the lattice oxygen of the metal oxide oxygen carrier in the encapsulated composite catalyst of the present invention effectively suppresses the defect of the zeolite molecular sieve being inactivated by carbon deposition due to diffusion limitation in micropores, thereby greatly improving the coke resistance of the encapsulated composite catalyst.

[0032] 4. The present invention applies encapsulated composite catalysts to the production of light olefins by oxidative cracking of naphtha, and utilizes the effect of lattice oxygen of oxygen carrier to decompose the cracking reaction into two gas-solid reactions (oxidation reaction and reduction reaction), thereby eliminating the energy- and capital-intensive air separation oxygen production process in the traditional oxidative cracking technology of naphtha, and avoiding the process of direct contact between naphtha hydrocarbons and gaseous oxygen in the traditional oxidative cracking process, thus eliminating potential safety hazards. At the same time, the selective hydrogen burning reaction of lattice oxygen in the reduction reaction step and the reoxidation of oxygen carriers in the air flow in the oxidation reaction step are both exothermic processes, which can supplement heat energy for the cracking reaction, realize the transformation of the cracking reaction from highly self-absorption of heat to self-heating, and greatly reduce process consumption.

[0033] 5. The present invention applies the encapsulated composite catalyst to the production of light olefins by oxidative cracking of naphtha, which not only reduces the reaction temperature, but also has high conversion rate, high quality selectivity of olefins, and less carbon deposition. The experimental results are shown in Tables 4 and 5.

[0034] The detailed structure of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a graph of application performance test data of Example 1; Figure 2 This is an application performance test data diagram of Example 2; Figure 3 This is an application performance test data diagram of Example 3; Figure 4 This is an application performance test data diagram of Example 4; Figure 5 This is a graph of application performance test data of Example 5. DETAILED DESCRIPTION

[0036] Example 1 CaMnO3 and CaMn 0.8 Cu 0.2 Synthesis of O3 Synthesis of CaMnO3: Ca(NO3)2 and Mn(NO3)2 with a stoichiometric ratio of Ca: Mn = 1:1 were dissolved in 40 mL of deionized water and stirred at 40 °C for 0.5 h. After the metal salts were fully dissolved, citric acid was added to the mixture with a molar ratio of 2.5:1 to the metal cations (Ca, Mn) using citric acid as a complexing agent, and stirred at 500 rpm and 40 °C for 1 h. Then, ethylene glycol (99.8%) with a molar ratio of 1:1 to citric acid was added, and then the mixture was heated to 85 °C and stirred until a sol was formed. The obtained solid product was placed in a 90 °C vacuum drying oven and dried overnight, and placed in a muffle furnace and programmed to 450 °C for calcination for 1 h, and then heated to 950 °C for calcination for 8 h (heating rate of 10 °C / min), cooled to room temperature and ground into a powdered solid less than 10 mesh, to prepare CaMnO3 perovskite composite oxide.

[0037] CaMn 0.8 Cu 0.2 Synthesis of O3: Ca(NO3)2, Mn(NO3)2, and Cu(NO3)2 with a stoichiometric ratio of Ca: Mn: Cu = 5:4:1 were dissolved in 40 mL of deionized water and stirred at 40 °C for 0.5 h. After the metal salts were fully dissolved, citric acid was added to the mixture at a molar ratio of 2:1 to the metal cations (Ca, Mn, Cu) using citric acid as a complexing agent, and stirred at 600 rpm and 50 °C for 2 h. Then, ethylene glycol (99.8%) was added at a molar ratio of 1.5:1 to citric acid, and the mixture was heated to 80 °C and stirred until the mixture formed a sol. The solid product was dried in a vacuum oven at 80 °C overnight, and then placed in a muffle furnace and heated to 400 °C for 2 h, and then heated to 1000 °C for 9 h (heating rate of 10 °C / min), cooled to room temperature and ground into a powdered solid with a particle size less than 10 mesh. 0.8 Cu 0.2 O3 perovskite composite oxide.

[0038] The CaMnO3 and CaMn prepared in Example 1 0.8 Cu 0.2 The O3 oxygen carrier was pressed into tablets, passed through a 20-40 mesh sieve, and loaded into a fixed bed reactor, and naphtha and nitrogen were introduced into the reactor. Under certain reaction conditions, a catalytic oxidation cracking reaction was carried out, and the reactant flow was separated to obtain the target product, low-carbon olefins. The specific catalytic reaction performance data are shown in Table 1. The perovskite oxygen carrier after the reaction was oxidized and regenerated in an air flow of 80 mL / min to replenish the consumed lattice oxygen.

[0039] The specific reaction conditions in this example are: 0.5 g of catalyst, reaction temperature of 800° C., space velocity of 25 mL / min, naphtha feed amount of 0.5 g, and reaction time of each redox cycle of 420 s.

[0040]

[0041] As can be seen from Table 1, the prepared perovskite composite metal oxide oxygen carrier has good naphtha conversion capacity and low-carbon olefin selectivity. 2+ B-doped CaMn 0.8 Cu 0.2 The O3 perovskite composite oxide increases the reaction activity and release rate of the surface lattice oxygen, improves the selectivity of the target product and reduces the formation of carbon deposition and coking.

[0042] Example 2 Synthesis of AMn2O4 (A = Ni, Mg) Synthesis of MgMn2O4: Mg(NO3)2 and Mn(NO3)2 with a stoichiometric ratio of Mg: Mn: Cu = 1:2 were dissolved in 20 mL of deionized water and stirred at room temperature for 1 h. After the metal salts were fully dissolved, citric acid was added to the mixture at a molar ratio of 1.5:1 to the metal cations (Mg, Mn) using citric acid as a complexing agent, and stirred at 400 rpm and 60 °C for 1.5 h. Then, ethylene glycol (99.8%) was added at a molar ratio of 5:2 to citric acid, and the mixture was heated to 90 °C and stirred until the mixture formed a sol. The obtained solid product was placed in a vacuum drying oven at 100 °C and dried overnight, and then placed in a muffle furnace and programmed to 500 °C for calcination for 2.5 h, and then heated to 900 °C for calcination for 6 h (heating rate of 10 °C / min), cooled to room temperature and ground into a powdery solid less than 10 mesh to prepare MgMn2O3 spinel composite oxide.

[0043] Synthesis of NiMn2O4: Ni(NO3)2 and Mn(NO3)2 with a stoichiometric ratio of Ni: Mn: Cu = 1:2 were dissolved in 30 mL of deionized water and stirred at room temperature for 1.5 h. After the metal salts were fully dissolved, citric acid was added to the mixture with a molar ratio of 3:1 to metal cations (Ni, Mn) using citric acid as a complexing agent, and stirred at 450 rpm and 55 °C for 2.5 h. Then, ethylene glycol (99.8%) with a molar ratio of 2:1 to citric acid was added, and then the mixture was heated to 70 °C and stirred until a sol was formed. The obtained solid product was placed in a 90 °C vacuum drying oven and dried overnight, and placed in a muffle furnace and programmed to 350 °C for calcination for 3 h, and then heated to 850 °C for calcination for 7 h (heating rate of 10 °C / min), cooled to room temperature and ground into a powdered solid less than 10 mesh, to prepare NiMn2O3 spinel composite oxide.

[0044] The AMn2O4 (A = Ni, Mg) oxygen carrier prepared in Example 2 was pressed into tablets, passed through a 20-40 mesh sieve, and loaded into a fixed bed reactor, and naphtha and nitrogen were introduced into the reactor. Under certain reaction conditions, a catalytic oxidation cracking reaction was carried out, and the reactant stream was separated to obtain the target product, light olefins. The specific catalytic reaction performance data are shown in Table 2. The perovskite oxygen carrier after the reaction was oxidized and regenerated in an air flow of 85 mL / min to replenish the consumed lattice oxygen.

[0045] The specific reaction conditions in this example are: 0.5 g of catalyst, reaction temperature of 800° C., space velocity of 25 mL / min, naphtha feed amount of 0.5 g, and reaction time of each redox cycle of 420 s.

[0046]

[0047] As can be seen from Table 2, the prepared spinel composite oxide has good naphtha conversion ability (conversion rate greater than 90%) and has a certain selectivity for light olefins, but the excessive conversion ability of the spinel composite oxide makes naphtha easy to peroxidize to form more carbon deposits and coke.

[0048] Example 3 Synthesis of Fe2O3, Mn2O3, Co3O4 Synthesis of Fe2O3: Dissolve ferric nitrate hexahydrate in 60 mL of deionized water, where Fe 3+ The molar concentration is 0.1 mol / L, recorded as solution A1; accurately weigh sodium carbonate and dissolve it in 60 mL of deionized water, where CO3 2- The molar concentration of Fe 3+ 3 times of the original solution, recorded as solution B1. Under vigorous stirring, solution B2 was added dropwise to solution A1 until the pH value of the solution was 10-11. The resulting mixed solution was stirred at 90 °C for 24 h, and then centrifuged and washed until neutral. The resulting solid product was dried at 70 °C overnight, calcined in a muffle furnace at 550 °C for 5 h, cooled to room temperature and ground into a powdered solid less than 10 mesh to prepare Fe2O3.

[0049] The synthesis of other metal oxide oxygen carriers (Mn2O3, Co3O4) is consistent with the above-mentioned Example 3. The Fe2O3, Mn2O3, and Co3O4 oxygen carriers prepared in Example 3 are pressed into tablets, passed through a 20-40 mesh sieve, and loaded into a fixed bed reactor, and naphtha and nitrogen are introduced into the reactor. Under certain reaction conditions, a catalytic oxidation cracking reaction is carried out, and the reactant stream is separated to obtain the target product, light olefins. The specific catalytic reaction performance data are shown in Table 3. The perovskite oxygen carrier after the reaction is oxidized and regenerated in an air flow of 90 mL / min to replenish the consumed lattice oxygen.

[0050] The specific reaction conditions in this example are: 0.5 g of catalyst, reaction temperature of 800° C., space velocity of 25 mL / min, naphtha feed amount of 0.5 g, and reaction time of each redox cycle of 420 s.

[0051]

[0052] As shown in Table 3, the prepared single-component metal oxide oxygen carrier has good naphtha conversion ability, but under high temperature reaction conditions, the metal oxide oxygen carrier is easy to sinter and agglomerate, resulting in low selectivity of light olefins and CO X And excessive carbon deposits.

[0053] Example 4 Synthesis of Metal Oxide-Molecular Sieve (Oxide Oxygen Carrier @ ZSM-5) Encapsulated Composite Catalyst Synthesis of CaMnO3@ZSM-5: 3 g of ZSM-5 was mixed with 1.46 g of tetraethyl orthosilicate (TEOS), 0.711 g of tetrapropylammonium hydroxide (concentration 40-50%) and 30 mL of aqueous solution, and the resulting mixture was stirred at 30 °C for 3 h to obtain a mixed suspension A2. The molar ratio of tetraethyl orthosilicate (TEOS) to tetrapropylammonium hydroxide was 1.0: 0.25. 1.5 g of CaMnO3 prepared in Example 1 above and 10.92 g of polyvinyl pyrrolidone (PVP) were dispersed in 30 mL of deionized water, and stirred at room temperature for 3 h until the mixture was uniformly dispersed to obtain a mixed suspension B2. The mixed suspensions A2 and B2 were mixed and heated to 90 °C and stirred vigorously for 5 h, and then the temperature was maintained and allowed to stand for 48 h. After aging, the mixed suspension was hydrothermally heated at 180 °C for 3 h. After the hydrothermal reaction was completed and cooled to room temperature, the mixed suspension was centrifuged and washed with deionized water three times. The solid product was dried in an oven at 120 °C for 12 h and calcined at 600 °C for 12 h (heating rate 5 °C / min), cooled to room temperature and ground into a powdered solid with a size less than 10 mesh to obtain the CaMnO3@ZSM-5 encapsulated composite catalyst.

[0054] Synthesis of NiMn2O4@ZSM-5: 2 g of ZSM-5 was mixed with 0.80 g of methyl orthosilicate (TMOS), 0.510 g of hexadecyltrimethylammonium bromide (CTAB) and 25 mL of aqueous solution, and the resulting mixture was stirred at 25 °C for 2.5 h to obtain a mixed suspension A3. The molar ratio of methyl orthosilicate (TMOS) to hexadecyltrimethylammonium bromide (CTAB) was 0.75:0.2. 1 g of NiMn2O4 prepared in Example 2 above and 13.65 g of polyvinylpyrrolidone (PVP) were dispersed in 25 mL of deionized water, and stirred at room temperature for 2 h until the mixture was uniformly dispersed to obtain a mixed suspension B3. The mixed suspensions A3 and B3 were mixed and heated to 85 °C and stirred vigorously for 3.5 h, and then the temperature was maintained and allowed to stand for 36 h. After aging, the mixed suspension was hydrothermally heated at 175 °C for 2 h. After the hydrothermal reaction was completed and cooled to room temperature, the mixed suspension was centrifuged and washed with deionized water three times. The solid product was dried in an oven at 110 °C for 10 h and calcined at 550 °C for 10 h (heating rate 5 °C / min), cooled to room temperature and ground into a powdered solid with a size of less than 10 mesh to obtain a NiMn2O4@ZSM-5 encapsulated composite catalyst.

[0055] Fe2O3@ZSM-5 1 g of ZSM-5 was mixed with 0.421 g of polyethoxydisiloxane (PEDS), 0.106 g of triethylamine and 20 mL of aqueous solution, and the resulting mixture was stirred at 20 °C for 2 h to obtain a mixed suspension A4. The molar ratio of polyethoxydisiloxane (PEDS) to triethylamine was 0.5:0.15. 0.5 g of Fe2O3 prepared in Example 2 above and 8.19 g of polyvinylpyrrolidone (PVP) were dispersed in 20 mL of deionized water, and stirred at room temperature for 1 h until the mixture was uniformly dispersed to obtain a mixed suspension B3. The mixed suspensions A3 and B3 were mixed and heated to 80 °C and stirred vigorously for 2 h, and then the temperature was maintained and allowed to stand for 24 h. After aging, the mixed suspension was hydrothermally heated at 170 °C for 1 h. After the hydrothermal reaction was completed and cooled to room temperature, the mixed suspension was centrifuged and washed with deionized water three times. The solid product was dried in an oven at 100 °C for 8 h and calcined at 500 °C for 8 h (heating rate 5 °C / min), cooled to room temperature and ground into a powdered solid with a size less than 10 mesh to obtain the Fe2O3@ZSM-5 encapsulated composite catalyst.

[0056] The encapsulated composite catalyst oxygen carrier prepared in Example 4 was pressed into tablets, passed through a 20-40 mesh sieve, and loaded into a fixed bed reactor, and naphtha and nitrogen were introduced into the reactor. Under certain reaction conditions, a catalytic oxidation cracking reaction was carried out, and the reactant stream was separated to obtain the target product, light olefins. The specific catalytic reaction performance data are shown in Table 4. The perovskite oxygen carrier after the reaction was oxidized and regenerated in an air flow of 80 mL / min to replenish the consumed lattice oxygen.

[0057] The specific reaction conditions in this example are: 0.5 g of catalyst, reaction temperature of 600° C., space velocity of 25 mL / min, naphtha feed amount of 0.5 g, and reaction time of each redox cycle of 420 s.

[0058]

[0059] As shown in Table 4, the encapsulated metal oxide-molecular sieve composite catalyst prepared by the hydrothermal seed induction method using ZSM-5 molecular sieve as the seed can effectively inhibit the sintering and agglomeration of metal oxide nanoparticles and reduce the CO X In addition, the lattice oxygen of the oxygen carrier inhibits the formation of coke through oxidation reaction, and promotes the forward movement of the cracking reaction through selective hydrogen burning reaction, thereby improving the reaction activity and selectivity of light olefins; the encapsulated composite catalyst in Example 4 is used in the production of light olefins by oxidative cracking of naphtha, which not only reduces the reaction temperature, but also has high conversion rate, olefin quality selectivity, and less carbon deposition.

[0060] Example 5 Metal oxide-molecular sieve (CaMn 0.8 Cu 0.2 O3@S-1、CaMn 0.8 Cu 0.2 O3@MCM-41、CaMn 0.8 Cu 0.2 Synthesis of O3@Beta) encapsulated composite catalyst CaMn 0.8 Cu 0.2 Synthesis of O3@S-1: 3 g of ZSM-5 was mixed with 1.06 g of silica sol, 0.174 g of cyclohexylamine and 30 mL of aqueous solution, and the resulting mixture was stirred at 30 °C for 3 h to obtain a mixed suspension A5. The molar ratio of tetraethyl orthosilicate (TEOS) to cyclohexylamine was 1.0:0.25. 1.5 g of CaMn prepared in Example 1 was added to the mixture. 0.8 Cu 0.2 O3 and 12.29 g polyvinyl pyrrolidone (PVP) were dispersed in 30 mL of deionized water, and stirred at room temperature for 3 h until uniformly dispersed to obtain a mixed suspension B5. The mixed suspensions of A5 and B5 were mixed and heated to 85 °C and stirred vigorously for 4 h, and then the temperature was maintained and allowed to stand for aging for 48 h. After aging, the mixed suspension was hydrothermally heated at 180 °C for 2 h. After the hydrothermal treatment was completed and cooled to room temperature, the mixed suspension was centrifuged and washed with deionized water three times. The solid product was dried in an oven at 110 °C for 12 h, and calcined at 550 °C for 12 h (heating rate 5 °C / min), cooled to room temperature and ground into a powdered solid less than 10 mesh to obtain CaMn 0.8 Cu 0.2 O3@S-1 encapsulated composite catalyst.

[0061] CaMn 0.8 Cu 0.2 Synthesis of O3@MCM-41: 2 g of MCM-41 was mixed with 0.954 g of methyltrimethoxysilane, 0.711 g of tetrapropylammonium hydroxide (concentration 40-50%) and 30 mL of aqueous solution, and the resulting mixture was stirred at 30 °C for 3 h to obtain a mixed suspension A6. The molar ratio of tetraethyl orthosilicate (TEOS) to tetrapropylammonium hydroxide was 1.0:0.25. 1.5 g of CaMn prepared in Example 1 was added to the mixture. 0.8 Cu 0.2O3 and 9.56 g polyvinyl pyrrolidone (PVP) were dispersed in 30 mL deionized water, and stirred at room temperature for 3 h until uniformly dispersed to obtain a mixed suspension B6. The mixed suspensions of A6 and B6 were mixed and heated to 80 °C and stirred vigorously for 5 h, and then kept at the temperature and aged for 40 h. After aging, the mixed suspension was hydrothermaled at 170 °C for 3 h. After the hydrothermal was completed and cooled to room temperature, the mixed suspension was centrifuged and washed with deionized water 3 times. The obtained solid product was dried in an oven at 120 °C for 8 h, and calcined at 600 °C for 9 h (heating rate 5 °C / min), cooled to room temperature and ground into a powdered solid less than 10 mesh to obtain CaMn 0.8 Cu 0.2 O3@MCM-41 encapsulated composite catalyst.

[0062] CaMn 0.8 Cu 0.2 Synthesis of O3@Beta: 2.5 g of Beta was mixed with 1.25 g of methyltriethoxysilane, 0.729 g of hexadecyltrimethylammonium bromide (CTAB) and 30 mL of aqueous solution, and the resulting mixture was stirred at 30 °C for 3 h to obtain a mixed suspension A7. Wherein, the molar ratio of tetraethyl orthosilicate (TEOS) to tetrapropylammonium hydroxide was: 1.0: 0.25. 1.5 g of CaMnO3 prepared in Example 1 above and 8.19 g of polyvinylpyrrolidone (PVP) were dispersed in 30 mL of deionized water, and stirred at room temperature for 3 h until uniform dispersion to obtain a mixed suspension B7. The A7 and B7 mixed suspensions were mixed and heated to 90 °C and stirred vigorously for 3.5 h, and then the temperature was maintained and allowed to stand for aging for 30 h. After aging, the mixed suspension was hydrothermally heated at 175 °C for 1 h. After the hydrothermal treatment was completed and cooled to room temperature, the mixed suspension was centrifuged and washed with deionized water three times. The solid product was dried in an oven at 115 °C for 11 h, calcined at 600 °C for 8 h (heating rate 5 °C / min), cooled to room temperature and ground into a powdered solid with a diameter less than 10 mesh to obtain CaMn 0.8 Cu 0.2 O3@Beta encapsulated composite catalyst.

[0063] The encapsulated composite catalyst oxygen carrier prepared in Example 5 was pressed into tablets, passed through a 20-40 mesh sieve, and loaded into a fixed bed reactor, and naphtha and nitrogen were introduced into the reactor. Under certain reaction conditions, a catalytic oxidation cracking reaction was carried out, and the reactant stream was separated to obtain the target product, light olefins. The specific catalytic reaction performance data are shown in Table 5. The perovskite oxygen carrier after the reaction was oxidized and regenerated in an air flow of 80 mL / min to replenish the consumed lattice oxygen.

[0064] The specific reaction conditions in this example are: 0.5 g of catalyst, reaction temperature of 600° C., space velocity of 25 mL / min, naphtha feed amount of 0.5 g, and reaction time of each redox cycle of 420 s.

[0065]

[0066] As shown in Table 5, the encapsulated metal oxide-molecular sieve composite catalysts prepared by using different molecular sieves as seeds combined with the hydrothermal seed induction method can effectively inhibit the sintering and agglomeration of metal oxide nanoparticles and reduce the CO X At the same time, the oxidation and reduction reactions of the lattice oxygen of the metal oxide oxygen carrier are exothermic reactions that can provide heat energy for the reaction system, which can effectively reduce the reaction temperature and enable it to obtain good naphtha conversion rate and low-carbon olefin selectivity under low temperature conditions.

[0067] The above is a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes according to the technical solutions and concepts of the present invention, which should be covered by the protection scope of the claims of the present invention.

Claims

1. An encapsulated composite catalyst, characterized in that: The encapsulated composite catalyst is composed of: oxide oxygen carrier@molecular sieve, wherein the oxide oxygen carrier is selected from CaMnO3, CaMn 0.8 Cu 0.2 Any one of O3, MgMn2O3, NiMn2O3, Fe2O3, Mn2O3, Co3O4, and the molecular sieve is any one of ZSM-5 molecular sieve, Silicate-1 molecular sieve and Beta molecular sieve.

2. The encapsulated composite catalyst according to claim 1, characterized in that: The preparation method of the encapsulated composite catalyst comprises: preparing CaMnO3, CaMn by a sol-gel method; 0.8 Cu 0.2 O3 perovskite metal oxide oxygen carrier or MgMn2O3, NiMn2O3 spinel oxide oxygen carrier, or Fe2O3, Mn2O3, Co3O4 single-component metal oxide oxygen carrier prepared by precipitation method, and then the encapsulated composite catalyst is prepared by hydrothermal seed induction method.

3. The encapsulated composite catalyst according to claim 2, characterized in that: The steps of preparing the encapsulated composite catalyst by the hydrothermal seed induction method include: adding 1-3 g of seed molecular sieve to a mixed solution of a silicon source, a template and 20-30 mL of deionized water to form a mixed aqueous solution, and stirring at 20-30°C for 2-3 h; then adding 0.5-1.5 g of an oxide oxygen carrier and 0.03-0.05 mol of a surfactant to 20-30 mL of deionized water, and stirring at room temperature for 1-3 h to obtain an oxide oxygen carrier mixed suspension; mixing the mixed aqueous solution with the oxide oxygen carrier mixed suspension to form a mixed system, stirring the mixed system at 80-90°C for 2-5 h to obtain a precursor mixed suspension, keeping the precursor mixed suspension warm for aging for 24-48 h, and then hydrothermally heating the precursor mixed suspension at 170-180°C for 1-3 h; centrifuging the precursor mixed suspension, washing with deionized water 2-4 times, and obtaining a solid product, and the solid product is heated at 100 After drying in an oven at ℃-120℃ for 8-12 h, the catalyst was calcined in a muffle furnace at 500-600℃ for 8-12 h, cooled to room temperature and ground into a powdered solid with a size of less than 10 meshes to obtain an encapsulated composite catalyst.

4. The encapsulated composite catalyst according to claim 3, characterized in that: The molar ratio of the silicon source to the template is 0.5-1.0: 0.15-0.

25.

5. The encapsulated composite catalyst according to claim 3, characterized in that: The silicon source is selected from any one of methyl orthosilicate, ethyl orthosilicate, silica sol, polyethoxydisiloxane, methyltrimethoxysilane and methyltriethoxysilane.

6. The encapsulated composite catalyst according to claim 3, characterized in that: The template agent is selected from any one of tetrapropylammonium hydroxide, hexadecyltrimethylammonium bromide, triethylamine and cyclohexylamine; and the surfactant is selected from polyvinyl pyrrolidone.

7. The encapsulated composite catalyst according to any one of claims 2 to 6, characterized in that: The sol-gel method comprises: preparing a perovskite or spinel oxygen carrier according to the molecular formula of CaMnO3, CaMn 0.8 Cu 0.2 O3, MgMn2O3, NiMn2O3, confirm the metal cation composition, and weigh the nitrate containing the corresponding cation and dissolve it in deionized water to form a nitrate solution, and then add citric acid and ethylene glycol to the nitrate solution to form a mixed system, and finally heat the mixed system at 70 ℃-90 ℃ with stirring to form a sol, and the sol is dried at 80 ℃-100 ℃, calcined at 350 ℃-500 ℃ for 1 h-3h, and calcined at 850 ℃-1000 ℃ for 6-9 h, and then cooled to room temperature and ground into a powdered solid less than 10 mesh to obtain oxide oxygen carriers doped with different metals.

8. The encapsulated composite catalyst according to any one of claims 2 to 6, characterized in that: The precipitation method comprises: weighing a nitrate of a single-component metal oxide oxygen carrier corresponding to a cation and dissolving it in deionized water, wherein the molar concentration of the metal cation is 0.1-0.2 mol / L, to obtain a metal precursor solution; then accurately weighing sodium carbonate and dissolving it in deionized water, wherein CO3 2- The molar concentration is 0.3-0.4 mol / L. Under stirring, the sodium carbonate solution is added dropwise to the metal precursor solution until the pH value of the mixed solution is 10-11. The mixed solution is continuously stirred at 90°C-100°C for 20-24h, and then centrifuged and washed until neutral. The obtained solid product is dried at 70°C-90°C overnight, and then calcined in a muffle furnace at 550°C-700°C for 5h-7h. After being cooled to room temperature, it is ground into a powdery solid less than 10 mesh to prepare a single-component metal oxide oxygen carrier.

9. A novel method for preparing light olefins by oxidative cracking of naphtha, characterized in that: The naphtha raw material is contacted with the catalyst, and an oxidative cracking reaction is carried out under the conditions of 500-800°C, an air flow rate of 25-200 mL / min, a naphtha feed amount of 0.1-0.5 g, and a reaction time of 300-420 s per redox cycle, and the reactant flow is separated to obtain the target product, light olefins; The catalyst is any one of the encapsulated composite catalysts in claims 1-8; Alternatively, the catalyst is selected from CaMnO3, CaMn 0.8 Cu 0.2 Any one of O3, MgMn2O3, NiMn2O3, Fe2O3, Mn2O3, Co3O4.

10. The novel method for preparing light olefins by oxidative cracking of naphtha according to claim 9, characterized in that: After the cracking reaction, the encapsulated composite catalyst is oxidized and regenerated by an air flow of 80-200 mL / min.

Citation Information

Patent Citations

  • Method for producing ethene and propene by catalytic oxidation cracking naphtha

    CN101190865A

  • Molecular sieve packaged multifunctional oxygen carrier as well as preparation method and application thereof

    CN114345397A

  • Hierarchical pore Beta molecular sieve packaged metal catalyst as well as preparation method and application thereof

    CN117085732A

  • Iron-containing small-grain ZSM-5 molecular sieve as well as preparation method and application thereof

    CN117658169A

  • Composite catalytic material as well as preparation method and application thereof

    CN118002190A